M MELATIH GURU UNTUK MENYUSUN MODUL PEMBELAJARAN BAHASA INDONESIA YANG INOVATIF - Nurhayati Siregar (LPPM Universitas Abdurrab, 2026)
The low quality of Indonesian language learning modules remains a significant challenge in efforts to improve educational quality. The modules commonly used are conventional in nature, focused on knowledge transfer, less contextual, and have not yet integrated competency-based and literacy-oriented approaches. This condition has led to low student participation and suboptimal development of critical thinking skills and integrative language competence. Theoretically, learning modules should be designed systematically, independently, and oriented toward meaningful learning activities, taking into account the principles of relevance, consistency, and adequacy of content aligned with learning outcomes. Nevertheless, limited teacher competence in designing innovative and adaptive modules remains a major obstacle. This Community Service Program (PKM) aims to enhance teachers’ ability to design innovative, contextual, and active learning-based Indonesian language modules. Competency strengthening focuses on understanding systematic instructional design, which includes needs analysis, goal formulation, material development, strategy selection, and evaluation, as well as the implementation of a constructivist approach that positions students as active subjects in learning. The program was carried out through several stages: needs analysis, delivery of conceptual materials, module development workshops, mentoring and feedback sessions, and evaluation of training outcomes. The training model applied an andragogical approach and guided teachers to integrate literacy, character education, differentiated instruction, and authentic assessment, referring to systematic principles and communicative competence in language teaching. The training results indicate a significant improvement in teachers’ understanding and skills in developing modules that meet the criteria of content, language, presentation, and graphical feasibility. The modules produced are more contextual, promote higher-order thinking skills (HOTS), integrate digital literacy, and implement project-based assessment in line with the principles of meaningful learning. Pedagogically and professionally, this program enhances teachers’ capacity in lesson planning, instructional material development, competency-based evaluation, and sustainable instructional innovation, thereby contributing to the improvement of adaptive and competency-oriented Indonesian language learning.